2022
DOI: 10.3389/fphar.2022.926104
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Quercetin and Its Analogs as Potent OXA-48 Beta-Lactamase Inhibitors

Abstract: Carbapenem resistance in Enterobacteriaceae caused by OXA-48 β-lactamase is a growing global health threat and has rapidly spread in many regions of the world. Developing inhibitors is a promising way to overcome antibiotic resistance. However, there are few options for problematic OXA-48. Here we identified quercetin, fisetin, luteolin, 3′,4′,7-trihydroxyflavone, apigenin, kaempferol, and taxifolin as potent inhibitors of OXA-48 with IC50 values ranging from 0.47 to 4.54 μM. Notably, the structure-activity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In this context, quercetin drew our attention because of its potential to inhibit both efflux pumps [35,36,39,58] and β-lactamases, including ESBL [59], OXA-48 [38], and MBLs [40]. In addition, we previously demonstrated that the structural modification of the quercetin scaffold could enhance its bioactivity, and di-F-Q (1) showed significant efflux pump inhibitory activity against MDR P. aeruginosa [37].…”
Section: -O-substituted Di-f-q (1) Showed Multitarget Inhibitory Acti...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, quercetin drew our attention because of its potential to inhibit both efflux pumps [35,36,39,58] and β-lactamases, including ESBL [59], OXA-48 [38], and MBLs [40]. In addition, we previously demonstrated that the structural modification of the quercetin scaffold could enhance its bioactivity, and di-F-Q (1) showed significant efflux pump inhibitory activity against MDR P. aeruginosa [37].…”
Section: -O-substituted Di-f-q (1) Showed Multitarget Inhibitory Acti...mentioning
confidence: 99%
“…In this context, di-F-Q (1; Figure 1) drew our attention because, compared with its parent compound (quercetin, 2; Figure 1) [35,36], di-F-Q (1) demonstrated significantly enhanced inhibitory activity against the efflux pumps of MDR P. aeruginosa [37]. Also interesting is that, albeit with low potency, quercetin (2) is capable of inhibiting β-lactamases [38][39][40]. Thus, it was anticipated that, based on the di-F-Q scaffold, a hereto unknown multitarget inhibitor might be designed which potentiates the antimicrobial activity of ATM against MDR MBL-producing P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has demonstrated the effective inhibitory activity of quercetin, 3',4',7-trihydroxyflavone, apigenin, and other flavonoids against OXA-48 [31]. Therefore, we further screened a flavone compound library containing 500 compounds for their ability to inhibit the hydrolysis of nitrocefin by purified OXA-48 enzyme.…”
Section: Inhibitory Activity Evaluationmentioning
confidence: 99%
“…In this context, plant secondary metabolites have drawn special attention because of their proven safety profiles along with their synergistic antibiotic-potentiating activity. 26−29 Quercetin (1, Figure 1) is one of those compounds investigated as an MDR reversal agent, and it has been recently reported to have the potential to inhibit both efflux pumps 30−32 and β-lactamases 33,34 including carbapenemases 35 and MBLs. 36 Recently, Pal and Tripathi reported that quercetin synergistically enhanced the antimicrobial activity of meropenem, carbapenem antibiotics, against carbapenem-resistant E. coli and K. pneumoniae presumably through inhibition of carbapenemases and efflux pump activity.…”
mentioning
confidence: 99%
“…Taken together, the discovery of safety-proven efflux pump inhibitors and MBL carbapenemase inhibitors are current challenges in the development of MDR reversal agents which can be utilized in the treatment of carbapenemases-resistant Gram-negatives. In this context, plant secondary metabolites have drawn special attention because of their proven safety profiles along with their synergistic antibiotic-potentiating activity. Quercetin ( 1 , Figure ) is one of those compounds investigated as an MDR reversal agent, and it has been recently reported to have the potential to inhibit both efflux pumps and β-lactamases , including carbapenemases and MBLs . Recently, Pal and Tripathi reported that quercetin synergistically enhanced the antimicrobial activity of meropenem, carbapenem antibiotics, against carbapenem-resistant E.…”
mentioning
confidence: 99%